Identification of three ookinete-specific genes and evaluation of their transmission-blocking potentials in Plasmodium berghei - Zheng, Wenqi (Vaccine, 2016)
With a renewed hope for malaria elimination, interventions that prevent transmission of parasites from humans to mosquitoes have received elevated attention. Transmission-blocking vaccines (TBVs) targeting the sexual stages are well suited for this task. Here, through bioinformatic analysis, we selected two putative Plasmodium berghei ookinete-stage proteins (PBANKA_111920, and PBANKA_145770) and a previously characterized ookinete protein PBANKA_135340 (PSOP7) for evaluation of their transmission-blocking potentials. Fragments of these predicted proteins were expressed in bacteria and purified recombinant proteins were used to immunize mice. Antisera against these recombinant proteins recognized proteins of predicted sizes from ookinete lysates and localized their expression on the surface of ookinetes. Inclusion of these antisera in in vitro ookinete culture significantly inhibited ookinete formation. Mosquitoes fed on mice immunized with the recombinant proteins also showed significantly reduced oocyst densities (60.0 – 70.7%) and modest reductions of oocyst prevalence (10.7 – 37.4%). These data, together with the conservation of these genes in Plasmodium, suggest that these three ookinete proteins could be new promising targets for TBVs and are worth of future investigations in the human malaria parasites.